2022
DOI: 10.3389/fonc.2022.957068
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in NENs, with a focus on gastroenteropancreatic NENs: from biology to current and future therapeutic implications

Abstract: Neuroendocrine neoplasms (NENs) are highly vascularized malignancies arising from cells of the diffuse neuroendocrine system. An intricated cross-talk exists between NEN cells and the tumor microenvironment, and three main molecular circuits (VEGF/VEGFR pathway, FGF-dependent signaling and PDGF/PDGFR axis) have been shown to regulate angiogenesis in these neoplasms. Multiple randomized trials have investigated antiangiogenic agents over the past two decades, and sunitinib is currently approved for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…In recent years, there has been a growing interest in incorporating new drugs from the MKI family into the NET management algorithm [5]. Although, to date, none of them have obtained favourable results or approval at a global level, a significant effort has been made in the design of clinical trials that continues today.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been a growing interest in incorporating new drugs from the MKI family into the NET management algorithm [5]. Although, to date, none of them have obtained favourable results or approval at a global level, a significant effort has been made in the design of clinical trials that continues today.…”
Section: Discussionmentioning
confidence: 99%
“…1. The most meaningful differential toxicities in each trial were as follows: liver toxicity with pazopanib (62% [95% CI 41-80] male versus 95% [95% CI 73-100] female, p 0.02), aphonia with sorafenibbevacizumab (50% [95% CI 32-68] male versus 11% [95% CI 2-36] female, p 0.01), face oedema with sunitinib (10% [95% CI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] male versus 41% [95% CI 27-58] female, p 0.0005) and bleeding with lenvatinib (0% [95% CI 0-13] male versus 21% [95% CI 8-44] female, p 0.0198) (Fig. 1).…”
Section: Sex-related Differences: Individual Mkimentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up was until November 2023. Genomic profiles for pNEN were clearer than epNEN, in which more abundant evidences demonstrated that molecular circuits regulating angiogenesis exerts a critical role throughout the development of pNEN ( 14 , 21 ). Furthermore, considering the differences in disease characteristics and indications, the included patients were divided into pNEN and epNEN patients, among whom the study analysis were made on surufatinib treatment cohort vs. sunitinib or everolimus (sunitinib + everolimus) treatment cohort for pNEN patients and surufatinib treatment cohort vs. everolimus treatment cohort for epNEN patients.…”
Section: Methodsmentioning
confidence: 99%